Genetic And Epigenetic Aspects of The Development of Congenital Surgical Pathologies in Newborns - Alexandrovna Ustimenko, Anna; Ilinichna Volkova, Anastasiia; Murmanovna Kokhreidze, Zinaida; Vladimirovna Korotkova, Anastasia; G. Petrenko, Elena; Alexandrovich Markov, Valery; Markov, Alexander (Journal of Neonatal Surgery, 2025)
Congenital surgical pathologies in newborns represent a serious medical problem, affecting both the quality of life of patients and the effectiveness of medical intervention. This paper investigates the genetic and epigenetic aspects of the formation of these pathologies in order to identify key The study analyzed mutations in genes responsible for morphogenesis and embryonic development (PAX6, SHH, FGF8), and investigated the influence of epigenetic factors such as DNA methylation and histone modifications. Bioinformatics analysis of genetic data, epigenetic profiling and clinical observations were used. The results show that the combination of inherited mutations and unfavorable epigenetic changes caused by environmental factors plays a key role in the development of congenital pathologies. This opens new perspectives for early diagnosis and targeted prevention methods.